Legal Consequences for Traffic Accident Perpetrators with Dead Victims - Lafri Prasetyono; A.A.A.N Tini Rusmini Gorda (Muhammadiyah University Press, 2021)
Objective: The purpose of the study is to determine the legal consequences for traffic accident perpetrators causing death and to investigate the legal considerations for perpetrators in criminal liability for traffic accidents.Method: The research used is empirical legal. This research employed sociological approach, legal approach, conceptual approach, and case approach. Research on the risk of traffic accidents is an observational study that surveys without any particular treatment given to the research subjects. The data used are primary data and secondary data. Primary data were obtained from the field through interviews. Secondary data were obtained through library research in the form of primary, secondary, and tertiary legal materials. The analysis technique in this research performed descriptive qualitative.Finding: The legal consequence for traffic accident perpetrators with death victims is a minimum of 5 years imprisonment, as per Article 359 of the Criminal Code. Legal considerations for perpetrators in criminal liability for traffic accidents comprise unintentional attribute (accident), those who have never been convicted, settlement between offender and victim, providing precise information, witnesses in mitigation, therefore the conviction can be reduced.Purpose: This study provides in-depth information about the Legal Consequences for Traffic Accident Perpetrators with Death VictimsNovelty/ Originality of the study: Legal Consequences for Traffic Accident Perpetrators with Death Victims